'Goldman-Sachs doesn't care if you raise chicken': the challenges of resistant prefiguration. (3rd September 2018) - Naegler, Laura
ABSTRACT: This article addresses debates in the 'post-Occupy movement' over the resistant potential of prefigurative politics, and asks how prefiguration can be conceptualized as resistance in relation to activists' understanding of politics, power and social change. Based on ethnographic fieldwork and interviews with activists in New York City, it looks at anarchist politics after Occupy Wall Street (OWS). Here, the absence of spectacular moments of confrontation and the removal of OWS's space of mobilization and organizing challenged activists to adjust their prefigurative politics to the shifting spaces post-Occupy. This paper advances our understanding of prefigurative politics by conceptualizing prefiguration as resistance in consideration of the elements of 'intent', 'recognition', 'opposition/confrontation' and 'creation'. Following this, it introduces the 'logic of subtraction' as a concept to understand the resistant potential of prefiguration. Here, I argue that rather than being in an antagonistic relationship with dominant power, resistant prefiguration aims for the creation of alternatives while subtracting power from the state, capital or any other external authority in order to render it obsolete. This understanding allows for a nuanced consideration of the proactive and creative potential of prefiguration, as well as of the difficulties of prefigurative practices in shifting movement spaces.